Sustainable Energy Solutions For Modern Mosques - Sahabuddin, Mohd Firrdhaus Mohd; Sabry, Shamimie Binti Mohd; Taib, Idris (MAJ - Malaysia Architectural Journal, 2024)
Sustainable Energy Solutions For Modern Mosques